Effectiveness of Central Pattern Generator Model on Developed One Legged Hopping Robot - Anuar , Mohamed Kassim; Miskon, Muhammad Fahmi (2011)
The paper presents the validity of using Central Pattern Generator (CPG) model to develop one leg hopping robot which hops higher and rhythmically. Infrared Ranging (IR) sensor is mounted on a platform to measure the distance of hopping performance. The distances of IR sensor from the platform to the floor in both static and vertical jumping motion are measured. MATLAB & Simulink model including CPG model is designed to evaluate the performance of IR sensor by converting the measurement data from IR sensor from voltage to distance by using function blocks. The result shows that the one leg hopping robot with CPG model is able to achieve maximum hopping height at 4cm.